الجزاء المترتب على إفشاء الصيدلي للسر المهني في التشريع الجزائري - العمري, صالحة (revue mofakir, 2018)
Legislator has committed Pharmacist to maintain professional secrecy as an Obligation in Article 113 and 114 of the Code of Medical Ethics, As well as Article 206 of the Health Law And it considered as a main crime committed by professionals Especially pharmacists, when they disclose the key of the secret ,as facts and information that he has been entrusted by the customer to others anyway, The legislature Spoke for this crime in the Penal Code in Article 301 he punishes from one month to 6 months and a fine 20.000 to 100.000 , Except the available cases are permissible under law. So it must raise awareness about this crime, and to inform people about the possibility of pursuing and punishing offenders.